Ultrasound-assisted osmotic process on quality of microwave vacuum drying sweet potato. Issue 11 (18th August 2018) - Lagnika, Camel; Huang, Jiapeng; Jiang, Ning; Li, Dajing; Liu, Chunquan; Song, Jiangfeng; Wei, Qiuyu; Zhang, Min
ABSTRACT: The effects of pretreatment before microwave vacuum drying (MVD) on texture, color, expansion, rehydration, drying rate, microstructure, sensory evaluation, and other properties of sweet potato were investigated in this study. The pretreatment consisted in five processing conditions, using blanching; osmotic dehydration at 35°Brix of sucrose (OD); ultrasound in distilled water (US); ultrasound in distilled water before osmotic dehydration (US + OD), and ultrasound-assisted osmotic dehydration (USOD). Pretreatments of sweet potato before MVD have shown success in reducing drying time with US treatment relatively more effective regarding drying time than other treatments. Compared with other treatments, US showed the highest rehydration ratio values. The osmotic group pretreatment exhibited a pronounced effect on water loss and solid gain, improved the color, aroma, and taste of dried sweet potato, whereas sucrose impregnation resulted in a hard texture observed with OD sample. USOD samples had a higher expansion ratio, lower hardness and color difference values, appeared less cell damaged, and recorded better overall quality than the other samples. There was a slight difference between USOD and US + OD samples. Combining osmotic dehydration with ultrasound as a pretreatment can significantly accelerate the heat transfer rate, reducing the dried time accordingly and increasing energy efficiency.